A Stress-Strain Model for Unconfined Concrete in Compression considering the Size Effect. (12th March 2019) - Yang, Keun-Hyeok; Lee, Yongjei; Mun, Ju-Hyun
Abstract : In this study, a stress-strain model for unconfined concrete with the consideration of the size effect was proposed. The compressive strength model that is based on the function of specimen width and aspect ratio was used for determining the maximum stress. In addition, in stress-strain relationship, a strain at the maximum stress was formulated as a function of compressive strength considering the size effect using the nonlinear regression analysis of data records compiled from a wide variety of specimens. The descending branch after the maximum stress was formulated with the consideration of the effect of decreasing area of fracture energy with the increase in equivalent diameter and aspect ratio of the specimen in the compression damage zone (CDZ) model. The key parameter for the slope of the descending branch was formulated as a function of equivalent diameter and aspect ratio of the specimen, concrete density, and compressive strength of concrete. Consequently, a rational stress-strain model for unconfined concrete was proposed. This model reflects trends that the maximum stress and strain at the peak stress decrease and the slope of the descending branch increases, when the equivalent diameter and aspect ratio of the specimen increase. The proposed model agrees well with the test results, irrespective of the compressive strength of concrete, concrete type, equivalent diameter, and aspect ratio of the specimen.